EFFECT OF HERBAL ADDITIVES ON LACTOSE STATUS OF MILK (International Journal of Food and Nutritional Sciences, 2022)
Lactose intolerance is a common problem among infants and adults, whereby the body fails to hydrolyse lactose due to the deficiency of the enzyme lactase leading to symptoms such as abdominal pain, intestinal gas, diarrhea, nausea, foul smelling stool, slow growth etc. Considering this difficulties, the present study was conducted to assess the efficiency of different medicinal herbs such as ginger, turmeric, cardamom, tea powder, coffee powder and anjal to hydrolyze lactose present in seven different kinds of milk such as cow milk, goat milk, buffalo milk, nanjil, Hatsun, Avin milk and Arokya milk inorder to find remedies for lactose intolerance. Lactose content of all the milk samples estimated spectrophotometrically using standard procedures revealed buffalo milk (80mg/ml) to be rich in lactose. Among the herbal additives tested for lactose reduction efficiency, ginger, tea and coffee exhibited highest activity specifically ginger was able to digest lactose in all kinds of milk used for the study.